Resource-constrained? Just wing it. - Singapore Management University (Institutional Knowledge at Singapore Management University, 2013)
Some four years ago, when the economic recession started in the West, Navi Radjou was convinced that the way ahead meant companies had to innovate and become faster, better and cheaper if they were to survive. Enter Jugaad. Jugaad is a Hindi word which means “an innovative fix; an improvised solution born from ingenuity and resourcefulness” and is now the name of a new approach to innovation.